Foreign direct investment and green innovation: driving low-carbon economic growth in China eastern provinces - Yunxiu, Qiu; Soo-Cheng, Chuah; Muda, Ruhaini (Faculty of Business and Management, 2025)
This study examines the effect of foreign direct investment (FDI), green technology innovation and economic growth on CO₂ emissions in eastern China. This study employs the extended STIRPAT model and the EKC model to analyze the relevant data of 12 provinces in eastern China from 2001 to 2021. The estimation methods of Pooled OLS, Fixed Effect and Random Effect are compared and analyzed using the static panel data analysis method. Finally, the robust standard error estimation method of the fixed effect is adopted. The robust standard error estimation results indicate that green technology innovation and economic growth have a negative impact on CO₂ emissions. In contrast, population growth rate and the proportion of secondary and tertiary industries have a positive effect. The impact of FDI on CO₂ emissions is found to be insignificant, suggesting that neither the Pollution Haven Hypothesis nor the Pollution Halo Hypothesis is prevalent in the eastern region of China. This suggests that the “inverted U-shaped” EKC does not exist in the eastern region of China. It is therefore evident that the enhancement of green technology innovation is of paramount importance for the reduction of CO₂ emissions in the eastern region.